EVOLUSI REGULASI GREEN HOSPITALITY: ANALISIS KOMPARATIF STANDAR SERTIFIKASI HOTEL DAN VILA DI INDONESIA - Ni Wayan Rena Mariani; I Made Darsana (CV. Lafadz Jaya, 2026)
This study aims to analyze the evolution of green hospitality regulations within hotel and villa certification standards in Indonesia during the 2013–2025 period. The growing emphasis on sustainable tourism development has encouraged the government to integrate environmental sustainability principles into the governance of accommodation businesses. However, studies examining the evolution of green hospitality provisions within hospitality regulations remain limited. This research employed a qualitative approach using document analysis combined with a normative legal perspective. The data consisted of four major regulations governing hotel and villa standards in Indonesia, namely the Ministerial Regulation of Tourism and Creative Economy No. 53 of 2013, No. 29 of 2014, No. 4 of 2021, and the Minister of Tourism Regulation No. 6 of 2025. Data were analyzed using qualitative content analysis based on four key dimensions of green hospitality: energy efficiency, water conservation, waste management, and green procurement. The findings reveal a significant transformation in Indonesian accommodation regulations, shifting from a service-quality orientation toward a sustainability-oriented regulatory framework. Waste management emerged as the most consistently regulated dimension across all regulations, while energy efficiency and water conservation demonstrated the most substantial development in recent regulations. In contrast, green procurement remains relatively underdeveloped. The findings indicate an increasing institutionalization of green hospitality principles within Indonesia’s tourism regulatory framework. The study contributes to the growing body of sustainable tourism literature and provides policy implications for strengthening hospitality certification standards in line with international sustainability practices.